A Phosphorus‐Doped Ag@Pd Catalyst for Enhanced CC Bond Cleavage during Ethanol Electrooxidation. Issue 47 (2nd November 2020) - Yang, Xiaobo; Liang, Zaipeng; Chen, Shuai; Ma, Minjun; Wang, Qiang; Tong, Xili; Zhang, Qinghua; Ye, Jinyu; Gu, Lin; Yang, Nianjun
Abstract: Ethanol is preferred to be oxidized into CO2 for the construction of a high‐performance direct ethanol fuel cell since this complete ethanol oxidation reaction (EOR) transfers 12 electrons. However, this EOR is sluggish and has the low activity as well as poor selectivity. To promote such a favorable EOR, more exactly the cleavage selectivity of CC bonds in ethanol, phosphorus‐doped silver‐core‐and‐Pd‐shell catalysts (denoted as Ag@PdP) are designed and synthesized. In the alkaline media, a Ag@Pd2 P0.2 catalyst is superior toward EOR into CO2 . It exhibits seven times higher mass activity and six times higher selectivity than the benchmark Pd/C catalyst. As confirmed by means of density functional theory calculation and in situ Fourier‐transform infrared spectroscopy, such high performance stems from an increased adsorption energy of OH radicals on the Pd active sites. Meanwhile, the tensile strain effect of a core–shell structure of this Ag@Pd2 P0.2 catalyst favors the formation of adsorbed CH3 CO intermediate, the key species for the enhanced C–C cleavage into CO2, instead of acetate. The proposed way to design and synthesize such high‐performance EOR catalysts will explore the practical applications of direct alkaline ethanol fuel cells. Abstract : Ethanol is electrochemically oxidized into CO2 on a phosphorus‐doped Ag @ Pd catalyst, featuring seven times higher mass activity and six times higher ethanol‐to‐CO2 selectivity than the benchmark Pd/C catalyst. Density functional theory calculation and electrochemical in situ infrared spectroscopic analysis confirm that such enhanced CC bond cleavage originates from the optimized formation of CH3 CO radicals and enhanced OH radicals adsorption on Pd active sites.